The transfer between the spending habits of different generations-a debate between retail and E-commerce - Diana-Elena ZIDARU (Theoretical and Applied Economics, 2024)

(untitled)
This study presents the transition from retail to E-commerce and the impact of this change on the global market, influenced by the advancement of technology, evolving human needs and the change in the mindset of the current generations activating in the field of trade for goods and services. Evaluating the shift of needs a consumer has over a prolonged period it can be observed how the big retailers won market share and how the trends in consumer spending were influenced by the advancement of technology from online marketing to fast shipping from any part of the world and where this movement is going.